PowToon: The Effect on Students Writing Descriptive Text - Damayanti, Wulan Aprilia; Wijayatiningsih, Testiana Deni; Ifadah, Muhimatul (UM Purwokerto Press, 2025)
The purpose of this study was to investigate the effect of PowToon on students' descriptive writing skills. A total of 38 students participated in this study. The method used was quasi-experimental. The measurement instruments used included a pre-test, post-test, and questionnaire. The average score of the experimental group before the test was 55.95, while the average score after the test was 80.86. Furthermore, the control group's mean pre-test score was 51.88, whilst their mean post-test score was 73.82. The post-test score of the experimental group increased much more significantly compared to the control group. The independent sample t-test yielded a result of 0.001< 0.05, indicating that there was a difference in the means of the two classes. The independent sample t-test also yielded a result of 0.001< 0.05, indicating that there was an increase in the means of the two classes. The results of the questionnaire regarding students' responses after using PowToon showed positive results, that the PowToon application help the students process more creative and it helped students to improve their writing skills. Moreover, this strategy did not only increased students’ writing skills but also increased students’ technological awareness through the use of PowToon. Further, it also includes improved classroom interaction strategies. In addition, the use of PowToon has been proven to improve students' writing skills, particularly in terms of content, organization, vocabulary, grammar, mechanics, and fluency.